The Effectiveness of Flashcard Games to Improve Vocabulary Mastery of Seventh Grade Students at SMPN 7 Palu - Ainun Rahmah; Aminah Suriaman; Maghfira Maghfira; Nadrun Nadrun (MASI Mandiri Edukasi, 2025)
This study aims to determine the effectiveness of flashcard games in improving the vocabulary mastery of seventh-grade students at SMPN 7 Palu. A quasi-experimental method with a pre-test and post-test control group design was employed. The participants consisted of two purposively selected classes: one serving as the experimental group, taught through flashcard games, and the other as the control group, receiving conventional instruction. Vocabulary tests were administered before and after the treatment to assess students’ improvement. The collected data were analysed using descriptive statistics and an independent-samples t-test at the 0.05 significance level. The findings revealed a significant difference between the post-test mean scores of the experimental group (79.42) and the control group (67.31), with a p-value of 0.000 (<0.05). These results indicate that the flashcard game effectively enhanced students’ vocabulary mastery. The use of visual and interactive media, such as flashcards, facilitated better word retention, understanding, and recall through dual coding of verbal and visual information. Moreover, the game-based activities increased students’ engagement and motivation during learning. In conclusion, flashcard games provide an effective and enjoyable medium for improving students’ English vocabulary mastery. It is recommended that English teachers integrate such interactive media into classroom instruction to foster more meaningful and engaging learning experiences.